Biological threat preparedness through vaccine development and stockpiling: challenges and strategic implications - Lee, Jungeun (Frontiers in Public Health, 2025)
Biological threat agents such as Bacillus anthracis, Variola virus, and botulinum toxin pose serious risk to national security and public health due to their high transmissibility, lethality, and potential for weaponization. This study analyzes the current status of vaccine development and strategic stockpiling for five biological agents—B. anthracis, Variola virus, Yersinia pestis, Vibrio cholerae, and botulinum toxin—which are believed to be potentially weaponized by North Korea. It reviews both traditional and next-generation vaccine platforms, including live-attenuated, inactivated, protein subunit, viral vector, DNA, RNA, and novel technologies such as self-amplifying RNA vaccine and advanced adjuvants. The study also examines the vaccine stockpiling strategies of major countries and international organizations, with a focus on key pathogens, logistical frameworks, and policy implications. Based on the findings, the paper highlights the need for enhanced global cooperation, public–private partnerships, and long-term investment to improve vaccine preparedness. Developing rapid deployment systems under military coordination, along with harmonizing international vaccine-sharing protocols, is considered essential for strengthening biodefense and emergency response readiness.